2016
DOI: 10.1055/s-0036-1583169
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Volumes during Pregnancy: A Systematic Review and Meta-Analysis of Observational Studies Assessing the Association with Infant's Birth Weight

Abstract: Objective This study aims to examine the association between different maternal physical activity exposures during pregnancy and infant's birth weight, body composition, and risk of inadequate weight. Methods Two reviewers (M.B. and J.L.G.) identified observational studies reporting total or leisure time activity during pregnancy and birth weight outcomes. Pooled analyses were performed to summarize the risk associated with high or moderate volumes of physical activity on birth weight. Results A total of 54 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 82 publications
(354 reference statements)
6
26
0
Order By: Relevance
“…The heterogeneity among studies limits the ability to pool published results. One meta‐analysis reports that ‘high’ physical activity levels were inversely associated with BW, but conversely ‘moderate’ physical activity levels were positively associated with BW. The included studies use different definitions of physical activity level and there is no standardisation with regard to the type and domains of activity or the volume, intensity, and timing.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity among studies limits the ability to pool published results. One meta‐analysis reports that ‘high’ physical activity levels were inversely associated with BW, but conversely ‘moderate’ physical activity levels were positively associated with BW. The included studies use different definitions of physical activity level and there is no standardisation with regard to the type and domains of activity or the volume, intensity, and timing.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing studies examining activity levels in pregnancy, particularly in the third trimester, is di cult due to variations in recording methods and de nitions. In most studies, PA is treated as a categorical variable, reported as a summary measure for the entire pregnancy or only reported in a single trimester (20). (10).…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise during pregnancy may elicit maternal and fetal adaptations with the potential for either positive or negative long-term effects on offspring. Regular exercise (moderate or vigorous activity) during pregnancy was associated with decreased risk of large infant size for gestational age (LGA) [28]. Reducing the risk of LGA by physical activity might indirectly mitigate LGA-induced complications.…”
Section: Discussionmentioning
confidence: 99%